If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -0.10(46) + 0.40x = 0.05(x + -8) Multiply -0.10 * 46 -4.6 + 0.40x = 0.05(x + -8) Reorder the terms: -4.6 + 0.40x = 0.05(-8 + x) -4.6 + 0.40x = (-8 * 0.05 + x * 0.05) -4.6 + 0.40x = (-0.4 + 0.05x) Solving -4.6 + 0.40x = -0.4 + 0.05x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.05x' to each side of the equation. -4.6 + 0.40x + -0.05x = -0.4 + 0.05x + -0.05x Combine like terms: 0.40x + -0.05x = 0.35x -4.6 + 0.35x = -0.4 + 0.05x + -0.05x Combine like terms: 0.05x + -0.05x = 0.00 -4.6 + 0.35x = -0.4 + 0.00 -4.6 + 0.35x = -0.4 Add '4.6' to each side of the equation. -4.6 + 4.6 + 0.35x = -0.4 + 4.6 Combine like terms: -4.6 + 4.6 = 0.0 0.0 + 0.35x = -0.4 + 4.6 0.35x = -0.4 + 4.6 Combine like terms: -0.4 + 4.6 = 4.2 0.35x = 4.2 Divide each side by '0.35'. x = 12 Simplifying x = 12
| x^2+7x+18= | | y=-3.3x+0.1 | | 6x=12/7 | | 25=8t(-2t+5) | | 3w/7=15 | | 169X^2=100 | | 0=6-5x | | x^2-20x-150=0 | | 169X=100 | | 8x-3(x-1)=28 | | x-3.5=-2y | | x+3.5=-2 | | (s^2+2s+10)=0 | | 8x-3x-3=28 | | 19/18x+1/18x | | a=ys+y | | 7(2x-3)=2(x+1) | | 7w+5+16w^2= | | y=2/5x+4/5 | | X^4-34x^2-225=0 | | 8x+1/9+17/18x | | -4(x-3)=5 | | x=-3+0.4615384615y | | 0=3x^2+4x-3 | | 9x^6-27x^4= | | 13/78=n/21 | | 4n-15=52 | | 44.1=6.3c | | (3y-2)(y+2)= | | -46-20t-12t-26=0 | | -(x^2)+2x+4=0 | | 7(9)-6y=33-2(9) |